Increased mortality after upper extremity fracture requiring inpatient care - Somersalo, Axel (Acta Orthop, 2015)
BACKGROUND AND PURPOSE: Increased mortality after hip fracture is well documented. The mortality after hospitalization for upper extremity fracture is unknown, even though these are common injuries. Here we determined mortality after hospitalization for upper extremity fracture in patients aged ≥16 years. PATIENTS AND METHODS: We collected data about the diagnosis code (ICD10), procedure code (NOMESCO), and 7 additional characteristics of 5,985 patients admitted to the trauma ward of Central Finland Hospital between 2002 and 2008. During the study, 929 women and 753 men sustained an upper extremity fracture. The patients were followed up until the end of 2012. Mortality rates were calculated using data on the population at risk. RESULTS: By the end of follow-up (mean duration 6 years), 179 women (19%) and 105 men (14%) had died. The standardized mortality ratio (SMR) for all patients was 1.5 (95% CI: 1.4–1.7). The SMR was higher for men (2.1, CI: 1.7–2.5) than for women (1.3, CI: 1.1–1.5) (p < 0.001). The SMR decreased with advancing age, and the mortality rate was highest for men with humerus fractures. INTERPRETATION: In men, the risk of death related to proximal humerus fracture was even higher than that reported previously for hip fracture. Compared to the general population, the SMR was double for humerus fracture patients, whereas wrist fracture had no effect on mortality.